The Level of Implementation Green Supply Chain Management (GSCM) Practices among Manufacturing Industry - Ahmad Saiful Saizan; Ramasamy, Chandrashekar (Research in Management of Technology and Business, 2024)
Green supply chain management (GSCM) procedures include purchasing, manufacturing, design, raw material selection, green distribution, and logistics, all of which are critical to implementing and minimising the firm’s internal and external pressures, as well as reducing errors and waste in operational processes. This study aims to investigate the level of implementation GSCM practices among manufacturing industry in Batu Pahat, Johor. The objectives are to identify the level of GSCM practices among manufacturing industry and to identify the level of operational performance among manufacturing industry. This study also aims to identify the relationship between GSCM practices and operational performances among manufacturing industry. Researcher has decided to conduct the survey at Batu Pahat, Johor. The target population of respondent for this study are the operations managers who involved in manufacturing sector around Batu Pahat, Johor. The researcher analysed the collected data quantitatively using Statistical Package for Social Sciences (SPSS) for descriptive analysis and also using correlation analysis. The questionnaire are established and distributed to target manufacturing industry. The results of this study discovered a strong relationship between GSCM practices and operational performance, indicating the major influence of customer collaboration on improving operational efficiency.